Effect of stacking faults on the optical properties of inverted opals - V. Yannopapas; N. Stefanou; A. Modinos (Physical Review Letters, 2001)
Stacking faults appear to be the most common type of defect in inverted opals which are good candidates for photonic crystals with absolute gaps in the visible range of light. In this Letter we present for the first time a systematic study of the effect of stacking faults on the optical properties of self-assembled photonic crystals, by means of large-scale transmittance calculations for macroscopic slabs of inverted opals with randomly distributed stacking faults. We show that frequency gaps, as seen in optical transmission experiments, will in general appear wider in the presence of stacking faults. We attribute the above to Anderson localization of light due to disorder.